Mathematical Connections in Statistics Student Worksheets - Salha Abu Bakar Salim Mahfud; Rachmaniah Mirza Hariastuti (Edunesia: Jurnal Ilmiah Pendidikan, 2022)
This research is development research conducted with the ADDIE development model, which aims to develop Student Worksheets (LKS) based on mathematical connections on statistical material for seventh-grade junior high school students. Data was collected by using questionnaires, interviews, and tests. The research respondents were 10 students consisting of 5 boys and 5 girls from SMP Al Irsyad Banyuwangi. Data analysis was carried out quantitatively and qualitatively. The results showed that the LKS based on mathematical connections met the valid criteria with a value of 4,53. LKS is also said to be practically based on the average student response which reaches more than 3,25. While the effectiveness of LKS is shown from classical completeness which reaches 90%. So that the product is declared fit for use. Furthermore, it is necessary to conduct trials with respondents on a large scale to determine their practicality and effectiveness